Street office and care practices: emerging conceptions and reflexivities - Joice Fabricio de Souza; Nilson Vieira Pinto; Thiago Medeiros da Costa Daniele; Mirna Albuquerque Frota; Karla Maria Carneiro Rolim (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To understand the perceptions of users of the "street office" about care practices. Methods: Mixed approach study carried out through semi-structured individual interviews with users of the "street office", with their reports analyzed through the Iramuteq software. Results: The general corpus of the reports consisted of 188 text segments (TS), with 178 TSs (94.68%), with three classes emerging: Class 1 - "Care understood by homeless people", with 85 TS (47.75%); Class 2 - "Satisfaction with access to health actions and services", with 40 TS (22.47%) and Class 3 - "Causes and coping with life on the street", with 53 TS (29.78%). The most recurrent word in the word cloud and in the analysis of similarity was "street", showing reflections on social inequality and health disparities. Conclusion: The narratives revealed the needs of users regarding their conceptions of care practices, constituting reflectivities emerging from this service instrument.